Application of Critical Discourse Analysis in a Poetic Text - Sharma, Bam Dev (Humanities and Social Sciences Journal, 2023)
Critical Discourse Analysis (CDA) has been one of the dominant research tools for textual analysis.It is mostly dealt through language and power relation in analysis as to how the surface of language embeds the power structural elements. In the beginning it was the part of Critical Linguistics and academic pursuits by Norman Flaircough (2010), Ruth Wodak (2006), Terry Lock (2004), Paul Gee (1999) and others expanded its horizons. As a result,several texts have been interpreted from the stand point of critical discourse analysis. Role of language, discourse, social interactions, ideology, power factors, and semiotic elements take account in the process of interpretation and explanation of a particular text. Based on the contextual premise, this article tries to explore how critical discourse analysis and how it is employed in the poetic text. For this purpose, this article analyzes a poem entitled " Shout" by Simon Armitage. Furthermore, the analytical approach consists of three dimensional components: The first is linguistic analysis, also known as textual analysis. The second is interpretative approach in which the text can be interpreted from social interactions as a form of discourse. And the third is explanatory in which the text can be interpreted from the perspective of power and ideology.